The receptor for advanced glycation end products is dispensable in a mouse model of oral and esophageal carcinogenesis - Mark, Regina; Lorenzo Bermejo, Justo; Bierhaus, Angelika; Plinkert, Peter K.; Angel, Peter; Heß, Jochen (Histology and histopathology, 2013)
Aberrant expression of the receptor for advanced glycation end products (RAGE) and its ligands, such as S100/Calgranulins, has been demonstrated in squamous cell carcinomas of the upper aerodigestive tract. However, the question whether RAGE signaling is causally linked with neoplastic transformation of keratinocytes in mucosal epithelia has not been addressed so far. We used the well-established mouse model of 4-nitroquinoline-1-oxide (4-NQO) induced tumorigenesis to investigate tumor development in control and RAGE-deficient (Rage(-/-)) animals. Although 4-NQO induced lesions of the tongue and the esophagus showed strong induction of the RAGE ligands S100a8 and S100a9, we did not observe any significant difference in tumor incidence or multiplicity between control and Rage(-/-) mice. Furthermore, detailed analysis of tumor sections by histological and immunohistochemical staining revealed no difference in either the size or histological architecture of dysplastic lesions, tumor cell proliferation, or the number of inflammatory immune cells in the tumor microenvironment. Finally, we detected induced transcript and protein levels of the Toll-like receptor 4 (Tlr4) in 4-NQO induced lesions, suggesting that signaling via the S100-Tlr4 axis may compensate for the lack of RAGE in early stages of tumor development. Our data demonstrate that RAGE is dispensable in the onset of genotoxic induced oral and esophageal squamous cell carcinoma and provide evidence for an alternative pathway of S100-Calgranulin signaling via Tlr4.